Building Teacher Performance through Work Facilities and Workload in Elementary Schools in Perumnas Antang - Andi Nabila Tenri Lala (GENTARA: management and accounting research, 2026)
Teacher performance plays a crucial role in determining the quality of education at the elementary school level, as teachers serve as key actors in delivering instruction and developing students’ competencies. However, teacher performance may be influenced by external factors such as work facilities and workload. This study aims to analyze the influence of work facilities and workload on teacher performance in elementary schools in Perumnas Antang. The research employed a quantitative approach using multiple linear regression analysis. The population consisted of all 34 elementary school teachers in Perumnas Antang, and a saturated sampling (census) technique was applied, meaning all population members were included as respondents. Data were collected through a Likert-scale questionnaire and analyzed using SPSS version 26. The results indicate that work facilities do not have a significant partial effect on teacher performance (t = 0.943; Sig. = 0.354 > 0.05), while workload has a significant effect (t = 4.807; Sig. = 0.000 < 0.05). Simultaneously, work facilities and workload significantly influence teacher performance (F = 13.672; Sig. = 0.000), with an R² value of 0.503, indicating moderate explanatory power